A study of plant species suitable for Riverside-Riparian Areas - Villa Juan, Jose Dan (Muhon : Journal of Architecture, Landscape Architecture, and the Designed Environment, 2005)
Transition zones between land and water environments are narrow strips of land called Riparian Areas having a distinct ecosystem. Ecologically, these areas hold great importance in regulating natural cycles between terrestrial and aquatic environments. However these zones are plagued with problems stemming from natural occurrences and those coming from manmade actions.